Současné využití a budoucnost kapslové kolonoskopie - Voška, M; Zavoral, M; Suchánek, Š (Rozhledy v chirurgii, 2017)
Colon capsule endoscopy (CCE) is a noninvasive technique for diagnostic imaging of the colon that does not require air insufflation or sedation. CCE can be used in average-risk patients, in patients with incomplete colonoscopy and in patients with contraindications for conventional colonoscopy. In this paper, we review the technical characteristics, current application and possible future development of CCE.Key words: colorectal cancer - screening colon capsule endoscopy.
Keywords: kolonoskopie; kapslová endoskopie; Colonoscopy; Humans; kolorektální nádory; lidé; Capsule Endoscopy; Colorectal Neoplasms